Rethinking Power and Human Management Practices: A Foucauldian and Psychopolitical Perspective - Velásquez, Nestor Raúl Porras (Nusantara Journal of Behavioral and Social Science, 2025)
This article examines the intersection of power relations and human management practices in modern organizations, utilizing a Foucauldian and psychopolitical framework. The objective is to explore how contemporary organizations employ psychological mechanisms, disciplinary techniques, and self-regulation strategies to influence employee behavior and professional identity. Unlike traditional hierarchical models of power, this study presents power as a relational and diffuse force embedded in organizational discourse, digital surveillance, and emotional governance. The research methodology involves documentary analysis of a range of materials, including academic literature, corporate policies, and case studies. This enables an exploration of how psychological discourse, performance evaluations, and corporate ideologies function as tools of control, shaping employee actions and identities. Findings suggest that modern organizations use subtle power mechanisms, such as emotional intelligence training and algorithmic management, to promote self-regulation and voluntary compliance with corporate expectations, rather than relying solely on coercion or direct authority. The study contributes to organizational studies, critical management theory, and industrial psychology by offering a comprehensive analysis of power in contemporary labor settings. It highlights how managerial control is internalized by employees, shaping their perceptions of autonomy and productivity. This research emphasizes the need for organizations to reconsider the ethical implications of surveillance, performance monitoring, and emotional labor management. Future research should explore alternative govern